Síndrome de Burnout e socialização organizacional : residentes de medicina - Flávia Fraga Silveira (2017)
Burnout syndrome is conceived as a response to chronic occupational stress that endemically affects help occupations professionals, including health professionals. Among them are the junior doctors who are professionals in the process of professional qualification. Organizational socialization refers to the content and learning process by which the individual develops the necessary attitudes, behaviors and knowledge in order to become a member of the organization. I aimed to identify the prevalence of burnout syndrome and to assess whether the process of organizational socialization of junior doctors is related to such prevalence. In the field activities, 273 resident physicians answered a socio-demographic and occupational profile, the MBI-General Survey and the Organizational Socialization Inventory (ISO). 13 of whom were interviewed. I submitted the answers of questionnaires to statistical analysis and those of interviews to content analysis. I found high emotional exhaustion (68.1%), moderate or high cynicism (41.7%) and moderate or high professional ineffectiveness (40.6%) among the participants. I identified the presence of Burnout syndrome in 25.64% of junior doctors, as well as its presence in different stages of development in 26.74% of the participants. The ISO results indicate that HC-UFMG junior doctors had predominantly moderate scores on six factors of organizational socialization and low on non-integration with the organization. The participants presented low (31.25%) or moderate (68.75%) scores on the integration factor to the people, which indicates that there are difficulties in this area. Burnout syndrome and organizational socialization presented low explanatory power relations with sociodemographic and occupational profile factors. I found a relationship between burnout syndrome and organizational socialization, in which the participants who presented the best ISO score had a lower incidence of burnout syndrome. I conclude that organizational investments in socialization would contribute to the prevention of burnout syndrome.